MANAGING GLYCEMIC RESPONSE IN NORMAL AND HYPERCHOLESTEROLEMIC SUBJECTS USING PSYLLIUM HUSK SUPPLEMENTED COOKIES - Tahira Batool Qaisrani; Masood Sadiq Butt; Khalid Masood Qaisrani et al. (Journal of University Medical & Dental College, 2017)
ABSTRACT: Objective: Present research was carried out to evaluate the efficacy of psyllium husk based dietetic cookies as therapeutic agent for management of blood glucose level in normal and hypercholesterolemic subjects. Methodology:Dietetic cookies were prepared by replacing wheat flour with psyllium husk. Five cookies with 3.22g dietary fibre and 1.61g arabinoxylan were provided to each (20) subject for two months twice a day along with control cookies (without psyllium husk) during two consecutive years study i.e. 2009-10 (Trial-I) & 2010-11 (Trial-II). Design: Two factor factorial under CRD was used for statistical analyses followed by Tukey test to compare means in efficacy study. Results: Significant differences in serum glucose concentrations in hypercholesterolemics due to treatment were obseved. Percent reduction in glucose ranged from 10.70 to 12.19% in TrialI &II, respectively. While serum HbA1c level was affected non-momentously due to treatment in this group. In healthy subjects, non-significant differences were observed in both traits. Conclusion: Psyllium husk enriched cookies are potent to be used as therapeutic food to manage hyperglycemia in hypercholestolemic subjects with soothening effect on healthy subjects.